Modulating the Ferromagnet/Molecule Spin Hybridization Using an Artificial Magnetoelectric. (10th May 2017) - Studniarek, Michał; Cherifi‐Hertel, Salia; Urbain, Etienne; Halisdemir, Ufuk; Arras, Rémi; Taudul, Beata; Schleicher, Filip; Hervé, Marie; Lambert, Charles‐Henri; Hamadeh, Abbass; Joly, Loïc; Scheurer, Fabrice; et al.
Abstract : Spin‐polarized charge transfer at the interface between a ferromagnetic (FM) metal and a molecule can lead to ferromagnetic coupling and to a high spin polarization at room temperature. The magnetic properties of these interfaces can not only alter those of the ferromagnet but can also stabilize molecular spin chains with interesting opportunities toward quantum computing. With the aim to enhance an organic spintronic device's functionality, external control over this spin polarization may thus be achieved by altering the ferromagnet/molecule interface's magnetic properties. To do so, the magnetoelectric properties of an underlying ferroelectric/ferromagnetic interface are utilized. Switching the ferroelectric polarization state of a PbZr0.2 Ti0.8 O3 (PZT) bottom layer within a PZT/Co/FePc‐based (Pc ‐ phthalocyanine) device alters the X‐ray magnetic circular dichroism of the Fe site within the phthalocyanine molecular top layer. Thus, how to electrically alter the magnetic properties of an interface with high spin polarization at room temperature is demonstrated. This expands electrical control over spin‐polarized FM/molecule interfaces, which is first demonstrated using ferroelectric molecules, to all molecular classes. Abstract : The interface between a ferromagnetic metal (Co) and a molecule (Fe phthalocyanine) can exhibit high spin polarization at room temperature. To control the magnetic coupling that underscores this promising spintronic property, the magnetoelectric properties at the neighboring interface between an oxide ferroelectric (PZT) and Co are used. This enables electrical control over the spintronic properties of any ferromagnet/molecule interface.